Single anchor node real-time positioning algorithm based on the antenna array - Yong Fu (International Journal of Distributed Sensor Networks)
This article presents an anchor node based on directional antenna array and reports the design of an automatic test system. The antenna radiation characteristics and the wireless channel model are studied first, followed by the evaluation of a single anchor node localization algorithm for wireless sensor network real-time positioning on the base of antenna radiation modeling and radio channel propagation model research then. Finally, the algorithm is evaluated by experiments in real environments. Experimental results show that the algorithm positioning accuracy could reach 1 m, and angular positioning accuracy error is less than 20° with no data exchange required during the positioning process. Hence, the wireless data transmission protocol complexity is reduced with improved real-time performance. This study is expected to provide technical references for the method research of wireless sensor network real-time positioning and new positioning system in practical applications.